Menganalisis Pengaruh Online Customer Review Terhadap Niat Beli Ulang Melalui Pendekatan SLR - Nurfadillah; Wardhana Haeruddin, Muhammad Ilham; Ichwan Musa, Muh.; Riu, Isma Azis; Abadi, Rahmat Riwayat (PT Maju Malaqbi Makkarana, 2025)
This study examines the influence of online customer reviews (electronic word-of-mouth eWOM) on repurchase intention through a Systematic Literature Review (SLR) approach. The main objectives are (1) to identify the mechanisms by which online reviews influence repurchase intention, (2) to summarize empirical findings and meta-analyses related to review attributes (valence, volume, quality, credibility, helpfulness), (3) to map mediators (e.g., trust, satisfaction, perceived usefulness) and moderators (e.g., product type, platform, culture), and (4) to identify research gaps and managerial implications. The SLR results consistently demonstrate that online reviews have a significant impact on purchase decisions and repurchase intentionthe effect is mediated primarily by customer trust and satisfaction, and moderated by product type (search vs. experience), platform, and review attributes (text quality, helpfulness, and review variance). Theoretical implications and practical recommendations are presented for researchers and digital marketers.